Chinese Personality - Center in a Network - Verner Worm (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2008)
This chapter try to highlight some key elements of Chinese thinking described from a cultural and philosophical perspective starting with explaining the background for Chinese philosophy, mainly Confucianism followed by central concepts such as holism (ying/yang) and a discussion of the concept of change that appears to be somewhat unique because of the central position change occupies in the Chinese philosophy. More specific, but still important concepts like face, guanxi, the Middle way and paradoxes way are also elaborated on. For reference comparison is now and then made to western philosophy when it is found to clarify Chinese thought. Comparative philosophy brings together philosophical traditions that have developed in relative isolation from one another and that are defined quite broadly along cultural and regional lines – Chinese versus Western is here chosen, but it is not to indicate that similar phenomena might not have appeared in other places in the world if not stated explicitly.
hdl:10398/7415
Keywords: 330; Persönlichkeitspsychologie; Kultur; Philosophie; Konfuzianismus; Holismus; Hierarchie; Soziales Netzwerk; China